Characterization of upper airway airflow dynamics in young adults with isolated Robin sequence: An exploratory investigation - Maria Noel Marzano-Rodrigues; Sergio Henrique Kiemle Trindade; Ivy Kiemle Trindade-Suedam (Journal of Oral Biology and Craniofacial Research)
Impaired upper airway dimension in adults with Isolated Robin Sequence (IRS) can alter airflow dynamics, increasing the risk of pharyngeal collapse and the onset of obstructive sleep apnea. This study aimed to characterize the upper airways of six young adults (20.83 ± 6.40 years) with IRS, using computational fluid dynamics. Upper airways of six patients were reconstructed using 3D segmentation, generating unstructured hybrid meshes with ≥4 million tetrahedral elements. Flow simulations at 15 l/min were solved using the realizable k-ε model and the finite volume method. Morphophysiological variables assessed were: total airway volumes, minimal cross-sectional areas, average pressure, velocity magnitude, wall shear stress, turbulent kinetic energy (k) production, and resistance. Airway volume corresponded to 29.32 ± 4.65 cm³ and minimal cross-sectional area was 1.00 ± 0.55 cm2. Pressure drop, airway resistance to airflow, velocity of the airflow and turbulent kinetic energy corresponded to 31.341 ± 15.837 Pa, 0.125 ± 0.063 (Pa s/ml), 1.882 ± 0.514 (m/s) and 0.152 ± 0.056 (m2/s2). The total airway volume exhibited a strong negative correlation with airway resistance (−0.899) and the inlet-to-outlet pressure drop (−0.899). The minimal cross-sectional area of the pharynx at the retroglossal level showed a strong negative correlation (−0.912) with the area-weighted average velocity magnitude of the airflow and with k production (−0.924). In conclusion, airway volume reduction and retroglossal obstruction in young adults with IRS are associated with altered fluid flow characteristics, including increased velocity magnitude, pressure drop, resistance, and turbulent kinetic energy production. These changes may increase the effort to breathe and predispose patients to sleep-disordered breathing.